Education for Sustainability in Universities: Challenges and Opportunities for Change. (17th March 2016) - Higgins, Blanche; Thomas, Ian
Abstract: Education for sustainability (EfS) is widely supported and researched; however, the broad and deep implementation of EfS in universities that is needed lags behind the goals of change agents. This article reviews literature on change procedures; in particular, curriculum change in universities. Our aim was to develop insights into strategies change agents can use to bolster their efforts to implement EfS. We found that change in universities is commonly acknowledged as a complex process, and that taking account of institutional culture is an integral step in curriculum change efforts. We also explored the struggles and successes of attempts to diversify the curriculum in order to find parallels that EfS change agents can learn from.